'All this for the Service of the King': Robert Wawayn and the Municipal Disturbances in Scarborough, 1307–1327. (3rd July 2021) - McCallum, Robin
Abstract : This article explores the disturbances in Scarborough in the early fourteenth century, which culminated in a failed attempt by burgesses to establish a rival civic government. Throughout the 1310s, prominent Scarborians began a dispute with Robert Wawayn, a fellow burgess and royal official who had seized power in the town. Drawing on the records of the royal commissions, it explores the disturbances and reveals how the two parties fought for supremacy. Wawayn defeated the rival government in 1319 after justices found that his opponents had instigated the disturbances. Despite accusations of corruption, he clung onto power until 1327 when Edward III reinstated Scarborough's privileges. This study sheds light on civic life and the problems of oligarchical rule in Scarborough, as well as the gradual inclusion of prominent townsmen into national government in the 1320s.